Cold Fish - Sono, Sion; Kimura, Shinya; Ashikawa, Makoto; Denden; Fukikoshi, Mitsuru (Third Window Films, 2011)
Although reportedly based on a true story, with its buckets of blood, screechy thesping and pervy air of hysteria, horror pic "Cold Fish" couldn't easily be mistaken for anything other than what it is: another fervid fantasia hatched by cult Japanese helmer Sion Sono. Yarn about a milquetoast fish store owner who gets sucked into the orbit of a psychotic serial killer and his equally wacko wife is, like most Sono pics, too long. But its gleeful humor and dare-you-to-watch aesthetic will help it rack up kills at specialty fests, and skewer followers on ancillary. [www.variety.com]
Keywords: DVD-Video